1981
DOI: 10.1002/bdd.2510020306
|View full text |Cite
|
Sign up to set email alerts
|

Isosorbide 5‐mononitrate pharmacokinetics in humans

Abstract: When isosorbide 5-mononitrate was intravenously infused at a rate of 4 mg h-1 for 2.5 h to five human subjects, its concentrations in plasma increased slowly to 185 ng ml-1 +/- 5 per cent C.V. at 2.5 h and a steady-state plasma level was not reached during the infusion. When the infusion was discontinued, plasma drug concentrations declined with an elimination half-life of 4.2 h +/- 6 per cent C.V. The systemic clearance after the infusion doses was 132 ml min-1 +/- 18 per cent C.V. and the volume of distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…The effect of food on the oral absorption of isosorbide-5-mononitrate While complete gastrointestinal absorption of isosorbide-5-mononitrate (IS-S-MN) has been shown in fasting subjects (Taylor et al, 1981; Abshagen et al, 1981), nothing is known about the influence of concomitant food intake on the pharmacokinetics of this drug. We measured plasma drug concentrations after a single oral dose of IS-S-MN in healthy human subjects, both fasting and after a standard breakfast.…”
mentioning
confidence: 99%
“…The effect of food on the oral absorption of isosorbide-5-mononitrate While complete gastrointestinal absorption of isosorbide-5-mononitrate (IS-S-MN) has been shown in fasting subjects (Taylor et al, 1981; Abshagen et al, 1981), nothing is known about the influence of concomitant food intake on the pharmacokinetics of this drug. We measured plasma drug concentrations after a single oral dose of IS-S-MN in healthy human subjects, both fasting and after a standard breakfast.…”
mentioning
confidence: 99%
“…Two earlier reports [4,16] of the pharma cokinetics of isosorbide 5-mononitrate have been complemented and extended by a more recent study involving a group of 12 healthy male volunteer subjects who received 20 mg of isosorbide 5-mononitrate orally as stan dard tablets or by intravenous infusion at a rate of 8 mg/h [17], During intravenous infu sion, mean plasma drug concentrations slowly reached 351 ± (SD) 41 ng/ml at the end of the infusion period of 2.5 h (fig. 3).…”
Section: Pharmacokineticsmentioning
confidence: 93%
“…2) [2,3]. Af ter absorption of an oral dose of isosorbide dinitrate from the gastrointestinal tract, ex tensive initial (first-pass) metabolism in the liver (and other tissues) converts about 50% of the dose to isosorbide 5-mononitrate, about 20% to isosorbide 2-mononitrate and about 25% escapes metabolism to reach the systemic circulation as the unchanged drug (4)(5)(6)(7), Studies in animals [8. 9] and in humans [10,11] have shown that the mononitrate metabolites share the pharmacological activ ity of the parent isosorbide dinitrate, al though they are probably intrinsically less potent.…”
Section: Introductionmentioning
confidence: 99%
“…Certainly previous data re garding isosorbide dinitrate have been en couraging [5]. Isosorbide mononitrate, how ever, has certain theoretical advantages over the dinitrate [6,7] and we therefore designed a study to explore the potential of isosorbide 5-mononitrate for the treatment of acute left ventricular failure in myocardial infarction. Since this was essentially a preliminary study we adopted an open protocol involving both intravenous and oral phases spanning a 48-hour period.…”
Section: Introductionmentioning
confidence: 99%